Enhancement of carotenoids and lipids production by oleaginous red yeast Sporidiobolus pararoseus KM281507 - Thanongsak Chaiyaso (2018)
© 2017 Taylor & Francis. Bioconversion of biodiesel-derived crude glycerol into carotenoids and lipids was investigated by a microbial conversion of an oleaginous red yeast Sporidiobolus pararoseus KM281507. The methanol content in crude glycerol (0.5%, w/v) did not show a significant effect on biomass production by strain KM281507. However, demethanolized crude glycerol significantly supported the production of biomass (8.64 ± 0.13 g/L), lipids (2.92 ± 0.03 g/L), β-carotene (15.76 ± 0.85 mg/L), and total carotenoids (33.67 ± 1.28 mg/L). The optimal conditions suggested by central composite design were crude glycerol concentration (55.04 g/L), initial pH of medium (pH 5.63) and cultivation temperature (24.01°C). Under these conditions, the production of biomass, lipids, β-carotene, and total carotenoids were elevated up to 8.83 ± 0.05, 4.00 ± 0.06 g/L, 27.41 ± 0.20, and 53.70 ± 0.48 mg/L, respectively. Moreover, an addition of olive oil (0.5 − 2.0%) dramatically increased the production of biomass (14.47 ± 0.15 g/L), lipids (6.40 ± 0.09 g/L), β-carotene (54.43 ± 0.95 mg/L), and total carotenoids (70.92 ± 0.51 mg/L). The oleic acid content in lipids was also increased to 75.1% (w/w) of total fatty acids, indicating a good potential to be an alternative biodiesel feedstock. Meanwhile, the β-carotene content in total carotenoids was increased to 76.7% (w/w). Hence, strain KM281507 could be a good potential source of renewable biodiesel feedstock and natural carotenoids.